Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Hasil Belajar Matematika Siswa Kelas IV SDN 90 Palembang - Maryeni, Yetri (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The TGT model is a learning method that involves students in teams to compete in learning activities. The aim of this research is to determine whether or not there is an influence of the application of the TGT learning model on the mathematics learning outcomes of class IV students at SDN 90 Palembang. The method used is True Experimental Design with a Posttest-Only Control Group Design. The population of all class IV students at SD Negeri 90 Palembang is 50 students. The population and sample were 26 students for the experimental class and 24 students for the control class. The data collection technique in this research is a test. The research data is in the form of posttest results with an average of 64.50 from the control class and 76.42 from the experimental class. Based on data analysis, the sample was normally distributed and homogeneous, the data was analyzed using the Independent Sample T-Test, resulting in a significance value of 0.002 < ɑ (α= 0.05) and tcount > ttable or 3.220 > 2.011, so reject Ho and accept Ha. So it can be concluded that there is an influence of the application of the TGT learning model on the Mathematics learning outcomes of class IV students at SDN 90 Palembang.